The Effect of Adding Epigallocatechin-3-gallate on the Porosity of Calcium Hydroxide - Ismiyatin, Kun; Saraswati, Widya; Sudarsono, Caeleb Fabrizio (Conservative Dentistry Journal, 2023)
Background: Dental caries is a very common non-communicablae disease found in all age groups and found in 3.5 billion people in the world. Caries that harm the pulp tissue can be treated by direct or indirect pulp capping. One of the physical properties possessed by pulp capping is the porosity of material. The material most often used for pulp capping treatment of pulp perforations is calcium hydroxide (Ca(OH) 2 ). However, Ca(OH) 2 has a high pH that caused the porosity to be low. High porosity can facilitate cell development and ion exchange. Thus, additional materials with a lower pH are needed to increase porosity such as Epigallocatechin-3-gallate (EGCG). However, the porosity of the combination of EGCG with Ca(OH) 2 is still unclear, so it needs to be researched. Purpose: To explain the differences of Ca(OH) 2 porosity after the addition of EGCG. Methods: This study used a laboratory experimental study with a post test only control group design. This research using 16 samples for each control (Ca(OH) 2 – aquadest) and treatment (Ca(OH) 2 –EGCG) group. Samples from each group were subjected to freeze drying, observed with SEM, analyzed with ImageJ software, and tested with independent T-test. Results: There was a significant difference (p<0.05) in the percentage of porosity between the addition of EGCG to Ca(OH) 2 namely 32,61% compared to Ca(OH) 2 with aquadest namely 23,38%. Conclusion: The porosity of the combination of calcium hydroxide with EGCG has a higher percentage compared to calcium hydroxide with aquadest.